A supplement to molecular data for five free-living marine nematode species of the family Comesomatidae Filipjev, 1918 (Nematoda: Chromadorida) from North Vietnam - Tu, Nguyen Dinh; Hien, Nguyen Thanh; Thanh, Nguyen Vu; Long, Phan Ke; Alexei, A. V. Tchesunov (Academia Journal of Biology, 2013)
Five species of Comesomatidae: Dorylaimopsis halongensis, Hopperia dolichurus, Paracomesoma lissum, Sabatieria doancanhi and Sabatieria praedatrix were identified based on morphological characters of males. To expose the systematic position of these comesomatids, we obtained nucleotide sequences of nuclear ribosomal DNA (D2/D3 and ITS region). The results showed the clear molecular differences between species in the Comesomatidae that proved to the morphology data.